Determining Optimal Parameters of Regular Microrelief Formed on the End Surfaces of Rotary Bodies - Dzyura, Volodymyr; Maruschak, Pavlo; Prentkovskis, Olegas (Algorithms, 2021)
The analytical dependences for determining the overlap area of V-shaped grooves of partially regular microrelief shifted by an angular pitch of 0.5° are established. The V-shaped grooves are formed on the end surface of the rotary body by vibration. In addition, the intersection between groove elements can be of different types. The relationship between the geometric parameters of V-shaped grooves and their location is determined. The influence of geometrical parameters of grooves on the overlap area is established depending on their location. Measures are proposed to ensure that the burnishing area is the same at different distances from the center of rotation of the rotary body end surface on which the partially regular microrelief is formed. A graph showing the dependence of the overlap area of two grooves on the axial pitch between them is constructed, and a block diagram of the algorithm for determining the optimal value of the axial pitch is developed.